1974
DOI: 10.1161/01.cir.49.6.1028
|View full text |Cite
|
Sign up to set email alerts
|

Ineffectiveness of Glucose, Potassium, and Insulin Infusion During Pacing Stress in Chronic Ischemic Heart Disease

Abstract: SUMMARYEight patients with coronary artery disease and positive exercise electrocardiograms undergoing cardiac catheterization were subjected to periods of atrial pacing-induced tachycardia at identical rates, before and during a glucose, potassium, and insulin (GKI) infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
1
26
1
Order By: Relevance
“…During ischemia and hypoxia, glycolysis is accelerated and glucose utilization is enhanced (4)(5)(6)(7)(8). Glucose-insulin-potassium infusions have been advocated for patients with acute myocardial infarctions and chronic ischemic heart disease; however, the efficacy of this treatment for limiting myocardial infarct size and left ventricular dysfunction still remains to be determined (3,(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…During ischemia and hypoxia, glycolysis is accelerated and glucose utilization is enhanced (4)(5)(6)(7)(8). Glucose-insulin-potassium infusions have been advocated for patients with acute myocardial infarctions and chronic ischemic heart disease; however, the efficacy of this treatment for limiting myocardial infarct size and left ventricular dysfunction still remains to be determined (3,(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Failure to consider the importance of potassium in the genesis of either the QRS or TQ-ST alterations may result in the inappropriate classification of certain interventions as efficacious when, in fact, they may be harmful. The observation that glucose-potassium-insulin administration reduced TQ-ST deflections (45) and histologic evidence of ischemic necrosis (46) is contrary to the clinical findings of Lesch et al (47) in which it was concluded that tolerance to ischemia was not extended but instead adversely affected by glucose-potassium-insulin administration.…”
Section: Discussionmentioning
confidence: 86%
“…Intracellular metabolites, primarily glycogen and glutamate, were labeled with I3 C by addition of [l- 13 C]glucose to the perfusate during a normoxk, preischemic period. 13 C and 31 P NMR spectroscopy was used to observe the metabolism of "C-labeled metabolites simultaneously with high-energy phosphorus metabolites and pH. The extent of acidosis and the rate and amount of labeled lactate accumulation during ischemia were the same in control (3 mM glucose + insulin) and GIK-treated hearts.…”
Section: I P Nuclear Magnetic Resonance Studymentioning
confidence: 99%
“…We report here the use of I3 C and 3I P NMR spectroscopy to correlate in time the metabolism of labeled carbon metabolites with changes in high energy phosphorus metabolites and pH during ischemia and reflow in the isolated Langendorff-perfused guinea pig heart. 13 C and 31 P spectra were collected on an alternate scan by guest on May 10, 2018 http://circres.ahajournals.org/ Downloaded from basis, 19 allowing us to observe metabolites containing phosphorus and carbon simultaneously on each heart. This combination is much more powerful than observation of either nucleus alone.…”
Section: I P Nuclear Magnetic Resonance Studymentioning
confidence: 99%